Increased Competitiveness of Indonesia's Rubber Rubber Exports After The Enactment of ACFTA (Asean-China Free Trade Agreement) - Febriani Febriani; Wisnu Hendra Kartika Aji; Didi Widia (Riviera Publishing, 2024)
The ASEAN-China Free Trade Agreement (ACFTA), which came into effect in January 2010, aims to increase economic cooperation and remove trade barriers. However, the value of Indonesia's rubber exports decreased significantly after the implementation of this agreement. This study uses the gravity model and Revealed Trade Advantage (RCTA) method to analyze the factors affecting the decline in the value of Indonesia's rubber exports. The data used covers the period 2001-2022 and is taken from various sources including TradeMap and interviews with rubber exporters. Findings show that the value of Indonesia's rubber exports to China and ASEAN countries has fluctuated, with a significant decline after 2011. Gravity model analysis shows that ASEAN-China real GDP growth is negatively related to the value of Indonesian rubber exports, while other factors such as exchange rates and commodity prices also play a role. The decline in Indonesia's rubber export competitiveness is not only caused by the implementation of ACFTA, but also by internal factors such as low productivity and underinvestment. Recommendations are given for commodity price adjustments to improve Indonesia's rubber export competitiveness.